A garland of forgotten goddesses : tales of the feminine divine from India and beyond - Slouber, Michael(ed.) (California University of California Press, 2021)
"Imagining the divine as female is rare, even controversial, in most religions. Hinduism, by contrast, preserves a rich and continuous tradition of goddess worship. A Garland of Forgotten Goddesses captures the diversity of this tradition by bringing together a fresh array of captivating and largely overlooked Hindu goddess tales from different regions. As the first such anthology of goddess narratives in translation, it highlights a range of sources from ancient myths to modern lore. The goddesses in this book battle demons, perform miracles, and grant rare Tantric visions to their devotees. Each translation is paired with a short essay that explains the goddess's historical and social context, demonstrating the ways religion changes over time"--
Includes bibliographical references and index.
Keywords: Hindu goddesses; Hinduism